Processing of Starfruit (Averrhoa bilimbi L.) on the Acceptability of Sweets as a Snack Food for Hypercholesterol Sufferers: Study of Color, Taste and Aroma - Prabowo, Agung; Irman, Dede; azahra, astrid Sulistya (Corespub, 2024)
This research aims to examine the acceptability of color, taste and aroma of candied starfruit (Averrhoa bilimbi L.) with three different formulations, namely fresh starfruit, dried candied and wet candied. The assessment was carried out by 30 trained panelists using the Hedonic Scale Scoring method. The analysis results show that there are significant differences in the acceptability of color and taste of sweets based on different formulations. Wet sweets (P3) received the highest assessment in all aspects, including color, taste and aroma. Although aroma plays an important role in determining the deliciousness of food, statistical test results show that sweet formulations do not significantly influence the perception of aroma by panelists. These results provide important insights in developing candied starfruit products that are more in line with consumer preferences.